2022
DOI: 10.1177/10567895211072580
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the fracture forming limits of bulk forming under biaxial tension

Abstract: The formability limits of bulk metal forming in principal strain space and in the effective strain vs. stress-triaxiality space are characterized by an uncertainty region in which cracks may be triggered by tension (mode I of fracture mechanics) or by out-of-plane shear (mode III). The problem in obtaining experimental data in this region has been known for a long time and the main objective of this paper is to present a new upset formability test geometry that can effectively contribute to the characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Competition between cracking opening modes by tension (mode I) and by out-of-plane shearing (mode III) in conventional bulk formability tests give rise to an 'uncertainty region' in principal strain space, as it was recently observed by Sampaio et al [1]. Although research on formability and crack opening modes has been taking the competition between crack opening modes into account, there are aspects related to material flow transitions in regions of bulk metal forming parts subjected to extensive plastic material flow that are not commonly taken into consideration.…”
Section: Introductionmentioning
confidence: 70%
“…Competition between cracking opening modes by tension (mode I) and by out-of-plane shearing (mode III) in conventional bulk formability tests give rise to an 'uncertainty region' in principal strain space, as it was recently observed by Sampaio et al [1]. Although research on formability and crack opening modes has been taking the competition between crack opening modes into account, there are aspects related to material flow transitions in regions of bulk metal forming parts subjected to extensive plastic material flow that are not commonly taken into consideration.…”
Section: Introductionmentioning
confidence: 70%
“…1) within which failure occurs by mixed modes resulting from competition between cracking by tension (mode I) and by out-of-plane shearing (mode III). This was recently confirmed by Sampaio et al [7], who designed a new test specimen to investigate the morphology of the cracks in the 'uncertainty region' of principal strain space and concluded that fracture was triggered by out-ofplane shearing (mode III) and propagate radially by tension (mode I). Transitions from crack opening by mode I to propagation by mode III at the leftmost corner of the 'uncertainty region' were previously observed by the authors during upset compression of cylindrical flanged test specimens made from aluminum AA2030-T4 [8].…”
Section: Introductionmentioning
confidence: 70%
“…In view of the above, Sampaio et al [7] proposed a new ductile damage criterion based on combination of the Cockcroft and Latham Although research on formability and crack opening modes has been directly, or indirectly, associated with stress triaxiality and, sometimes, also with the Lode parameter [11], there are aspects related to material flow transitions that are not commonly taken into consideration. Accountability of these aspects means, in practical terms, to include the three-dimensional to plane stress material flow transitions (i.e., bulk-to-sheet evolutions) in the list of parameters that are responsible for the competition between the different crack opening modes.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Sampaio et al 14 with the new barreled ring test specimen also underlined the existence of an “uncertainty region” (refer to the orange-shaded region in Figure 1(b)) in which cracks may open by mixed modes resulting from combination of modes I (by tension) and III (by out-of-plane shear).…”
Section: Introductionmentioning
confidence: 75%
“…Modeling the fracture forming limits in bulk forming resulting from cylindrical, tapered, flanged, and barreled ring formability tests with the ductile fracture criterion (adapted from Sampaio et al 14 ).…”
Section: Introductionmentioning
confidence: 99%